2024
DOI: 10.2174/2772434418666230331083714
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Intravenous Remdesivir to Prevent Progression to Severe COVID-19: An Observational Study from a Greek Hospital

Abstract: Background: Remdesivir, a viral RNA polymerase inhibitor, has been a powerful weapon in the battle against the SARS-CoV-2 pandemic. Originally approved for use in hospitalized patients, remdesivir improves clinical outcomes in patients with moderate to severe coronavirus disease 2019 (COVID-19). After proving efficacious in hospitalized patients, its use was approved in early disease for symptomatic, non-hospitalized patients that present risk factors for progression to severe disease. Methods: We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Currently, a limited number of real-life studies have demonstrated that the early administration of remdesivir has a good safety profile and significantly reduces the risk of COVID-19 disease progression and mortality among high-risk patients in the era of the omicron variant ( 14 , 16-18 ). A recent study focused on non-hospitalized vaccinated high-risk patients and demonstrated that a 3-day course of remdesivir resulted in a 75% lower possibility of hospitalization and 95% of respiratory failure, with favourable outcomes in cases that required hospitalization ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a limited number of real-life studies have demonstrated that the early administration of remdesivir has a good safety profile and significantly reduces the risk of COVID-19 disease progression and mortality among high-risk patients in the era of the omicron variant ( 14 , 16-18 ). A recent study focused on non-hospitalized vaccinated high-risk patients and demonstrated that a 3-day course of remdesivir resulted in a 75% lower possibility of hospitalization and 95% of respiratory failure, with favourable outcomes in cases that required hospitalization ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from pivotal studies, limited real-world data supporting the effectiveness of early remdesivir therapy in decreasing the overall risk of hospitalization and disease progression in SARS-CoV-2 high-risk outpatients are currently available ( 14 , 15 ). In addition, real-life data focusing on the safety and effectiveness of early remdesivir among the elderly are limited.…”
Section: Introductionmentioning
confidence: 99%